THE ROLE OF UZBEK CUISINE IN OUR NATIONAL CUISINE - Mavlyuda Khamzaevna Faizullaeva (Scholar Express Journal, 2021)
One of the most actively studied topics in the world of anthropology today is the culture of nutrition. The article tries to move from the traditional ethnographic description of food to a modern complex related to the views of today's humanitarian, social and natural spheres. The national cuisine has always been and will remain a unique object of study of classical ethnography.
Keywords: Food; nutrition or eating; material culture; anthropology